Print Quality Analysis of Stone Paper and Coated Sticker Paper Used in Screen Printing - AKGÜL, AHMET (My University, 2024)
The sustainable use of natural resources is becoming an increasingly important issue today. Stone paper, produced as an alternative to cellulose-based paper from the forest, is rich in minerals and produced without cellulose and water. This study focuses on the behavior of screen-printing ink on two different papers, stone paper and coated sticker paper. Properties such as ink adhesion, rubbing resistance, optical printing ink density, ink consumption, and lightfastness were measured on these surfaces. Solvent- and UV-based inks were used, and printing was carried out on cellulosebased (coated sticker paper) and mineral-based (stone paper) paper layers using three different mesh counts (90, 120, and 140 tpc). The rubbing resistance and lightfastness of the papers were also measured. The present findings revealed that stone paper had the same printability properties as cellulose-based paper. The study concluded that using a 140 tpc mesh with both types of ink results in a high-lightfastness ink layer and lower ink consumption. UV-based inks exhibited high rub resistance across all mesh counts. Additionally, when printing with stone paper, there will be a reduction in ink consumption, thereby achieving cost savings. Based on the present findings, it was concluded that water- and oil-resistant stone paper can be considered an essential alternative in many fields, including the printing industry. Keywords: stone paper; lightfastness; rub resistance; screen printing; printability; printing substrate
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); stone paper; lightfastness; rub resistance; screen printing; printability; printing substrate